Open Educational Resources (OER) - Weber, Tassja (Praxishandbuch Hochschullehre II)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Commutator-free Cayley methods - Wembe Moafo, Boris Edgar; Offen, Cristian; Maslovskaya, Sofya; Ober-Blöbaum, Sina; Singh, Pranav (J. Comput. Appl. Math)
Differential equations posed on quadratic matrix Lie groups arise in the context of classical mechanics and quantum dynamical systems. Lie group numerical integrators preserve the constants of motions defining the Lie group. Thus, they respect important physical laws of the dynamical system, such as unitarity and energy conservation in the context of quantum dynamical systems, for instance. In this article we develop a high-order commutator free Lie group integrator for non-autonomous differential equations evolving on quadratic Lie groups. Instead of matrix exponentials, which are expensive to evaluate and need to be approximated by appropriate rational functions in order to preserve the Lie group structure, the proposed method is obtained as a composition of Cayley transforms which naturally respect the structure of quadratic Lie groups while being computationally efficient to evaluate. Unlike Cayley-Magnus methods the method is also free from nested matrix commutators.

Three-Phase Instantaneous Current Controller for Unbalanced Grid Inductors Without DQ Transform for Cascaded H-Bridge Converters - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2025 Energy Conversion Congress & Expo Europe (ECCE Europe))
Three-phase cascaded H-bridge converters (CHBs) in star configuration require reliable current controllers to evenly charge the module DC-link capacitors. Conventionally, a current control in dq-coordinates is utilized. At steady state, the resulting calculated reference arm voltages are sinusoidal, have identical amplitudes and show a phase shift of 120 degree to each other. For balanced grid inductors, the resulting grid currents also have the same amplitude. However, own simulations show that unbalanced grid inductors always lead to different grid current amplitudes (4% difference in this case). As a result, the averaged charging module powers differ and the peak DC-link capacitor voltage rises as well. In the first step, an adaptation of an existing zero-sequence voltage injection is proposed. For balanced grid inductors, it converges to the 3rd harmonic voltage injection which can reduce the peak-to-peak DC-link voltage ripple up by to 50% and balances the power between the phases. However, unbalanced grid inductors still lead to the same unbalanced grid currents of 4%. Therefore, a new method with 4 integrators based on linear regression is proposed to achieve sinusoidal grid currents for unbalanced inductors. The proposed method has a similar transient dynamic as the conventional dq control, but balances the grid currents nearly ideally. Simulation results of a 1MW cascaded H bridge and a scaled-down prototype verify the proposed method.
Keywords: Cascaded H-Bridge; Current Control; dq Transformation; Linear Regression; Unbalanced Inductors

Microscopic approach to the quantized light-matter interaction in semiconductor nanostructures: Complex coupled dynamics of excitons, biexcitons, and photons - Rose, Hendrik; Schumacher, Stefan; Meier, Torsten (Physical Review B)

Unterrichtsintegrierte Diagnostik im Förderschwerpunkt Sprache – ein Überblick - Jonas, Kristina; Abel, Miriam Katharina (Sprachförderung und Sprachtherapie in Schule und Praxis)

Modelling, Argumentation and Problem-Solving in the Context of Outdoor Mathematics - Jablonski, Simone

The Impact of a MOOC: Long-Term Analysis of Teachers' Learning Outcomes and Practices - Taranto, E; Jablonski, S; Recio, T; Cunha, E; Ludwig, M; Mammana, MF

"Sohn, dein Blut muß ich vergießen" - Ritual und Opfer in den Abraham-Oratorien des 19. Jahrhunderts - Höink, Dominik; de Vos, J. Cornelis (Musik im Ritual - Rituale in der Musik)

"In nomine Domini". Zum 100. Geburtstag des Komponisten Giselher Klebe - Höink, Dominik (Musik & Kirche)

Friedrich Schneider, Christus der Meister. Oratorium in drei Teilen. Partitur

Digitalisierung und Künstliche Intelligenz - Steinhardt, Isabel (Hochschulforschung)
In diesem Beitrag wird ein Überblick gegeben, welche Forschung zu Digitalisierung und künstliche Intelligenz (KI) in den Bereichen Verwaltung, Forschung, Studium und Lehre sowie Governance von Hochschulen besteht. Der Fokus liegt hierbei auf aktuellen Forschungsergebnissen seit der Coronapandemie. Zentral sind Fragen nach Effektivität und Effizienz durch Digitalisierung und KI und danach, wie Verbesserungen angestoßen werden können.
Keywords: Digitalisierung; Künstliche Intelligenz; Forschung; Lehre; Governance; Verwaltung

Open Science - Steinhardt, Isabel; Röwert, Ronny (Hochschulforschung)
In diesem Beitrag wird zunächst die historische Entstehung von Open Science kurz skizziert und definiert, was unter diesem Begriff zu verstehen ist. Daran anschließend werden die Open-Science-Praktiken Open Data, Open Access, Open Source, Open Methodology und Open Peer Review dargestellt und diskutiert, welche Forschungserkenntnisse zu Open Science vorhanden sind. Im Schluss werden Forschungsdesiderate aufgegriffen und die Implikationen von Open Science für die Wissenschaft erläutert.
Keywords: Open Data; Open Access; Open Source; Open Methodology; Open Peer Review

Quantum teleportation with dissimilar quantum dots over a hybrid quantum network - Laneve, Alessandro; Ronco, Giuseppe; Beccaceci, Mattia; Barigelli, Paolo; Salusti, Francesco; Claro-Rodriguez, Nicolas; De Pascalis, Giorgio; Suprano, Alessia; Chiaudano, Leone; Schöll, Eva; Hanschke, Lukas; Krieger, Tobias M.; et al. (Nature Communications)

Teaching Hypotheses with Émilie du Châtelet - Hagengruber, Ruth Edith; Velema, Floris (Journal of Didactics of Philosophy)

KI als Herausforderungen für die qualitative Methodenlehre – ein Diskussionsaufruf! - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Rezension von Simone Amorocho (2024): Mündliche Prüfungen in der Pflegeausbildung. Eine gesprächsanalytische Studie zu sprachlichen und interaktionalen Anforderungen - Prikoszovits, Matthias

Photorefraction and in-situ optical cleaning in various types of LiNbO3 waveguides - Kirsch, Michelle; Kießler, Christian; Lengeling, Sebastian; Stefszky, Michael; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine (Optics & Laser Technology)
Lithium niobate (LiNbO3) is a widely used material with several desirable physical properties, such as high second-order nonlinear optical and strong electro-optical effects. Thus LiNbO3 is used for various applications such as electro-optic modulation or nonlinear frequency conversion and mixing. But LiNbO3 also exhibits a strong photorefractive effect, which limits the intensity of the optical fields involved. Various approaches to reduce the photorefractive effect have been investigated, such as increasing the temperature, doping the crystal or using different waveguide designs in LiNbO3. Here, we present an analysis of the approach to increase the photorefractive damage threshold by using different waveguide designs. Contrary to previous claims and investigations, our SHG measurements revealed no significant difference in resistance to photorefractive damage when comparing conventional Ti-doped channel waveguides and Ti-doped diced ridge waveguides in LiNbO3. Furthermore, we have investigated the effect of photorefractive cleaning and curing using a light field at 532 nm. Here, we observe a reduction in the photorefractive effect at room temperature during and after SHG measurements, which is an easy alternative to conventional approaches.

La corte como mare errorum en La Cisma de Ingalaterra - Schlieper, Hendrik (Cálculo y error. Recontando a Calderón. XX Coloquio Anglogermano sobre Calderón)

Facilitating the Automated Generation of Data-Driven Models for the Diagnostics and Prognostics of Technical Systems - Löwen, Alexander; Quirin, Dennis; Hesse, Marc; Aimiyekagbon, Osarenren Kennedy; Sextro, Walter (2025 IEEE 30th International Conference on Emerging Technologies and Factory Automation (ETFA))
The integration of data-driven models and specifically machine learning for conditon monitoring and predictive maintenance into companies, especially small and medium-sized enterprises, offers significant opportunities in reducing costs, operating more sustainably, and maintaining long-term competitiveness. However, many small and medium-sized enterprises lack the necessary resources and expertise to derive knowledge from data and integrate their own machine learning based solutions. To address this challenge, a framework is presented that enables the automated generation of data-driven models with a particular focus on condition monitoring and predictive maintenance, but applicable to other use cases as well. Using a dataset from the 2022 data challenge of the prognostics and health management society, it is demonstrated that the framework can generate high-performing models, achieving F1-scores up to 0.998, exemplarily for a classification task.

Professionelle Wahrnehmung der Anforderungssituation 'Gespräche zum flexiblen Rechnen moderieren': Ein Vergleich zwischen angehenden und erfahrenen Lehrkräften mittels Epistemic Network Analysis - Becker, Federica
Im Beitrag wird die professionelle Unterrichtswahrnehmung von (angehenden) Lehrkräften bezogen auf die Anforderungssituation 'Gemeinsam Gespräche moderieren' im Kontext des flexiblen Rechnens in Jahrgangsstufe 1 betrachtet. Die Studie untersucht mittels Videovignetten expertise-bezogene Unterschiede in der professionellen Wahrnehmung, indem je 10 angehende und erfahrene Mathematiklehrkräfte betrachtet werden. Die zunächst inhaltsanalytisch ausgewerteten Daten der beiden Gruppen werden mittels der epistemischen Netzwerkanalyse verglichen. Es werden erste Ergebnisse berichtet.